2019
DOI: 10.1002/pits.22247
|View full text |Cite
|
Sign up to set email alerts
|

The relation of social skills and school climate of diversity to children's life satisfaction: The mediating role of school connectedness

Abstract: The present study examined the role of school connectedness in mediating the relations of social skills and school climate of diversity (SCD) to life satisfaction (LS) among school‐aged children. This study also investigated whether there is any gender difference in relationships. Participants included 873 elementary school students in Grades 4 through 6. The results of the structural equation modeling supported the partial mediating role of school connectedness, indicating that social skills and SCD lead to L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
(94 reference statements)
2
15
0
1
Order By: Relevance
“…Items are rated on a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). A range of Cronbach's alphas have been reported for this subscale: .70 (Carney, Liu, & Hazler, 2018), .74 (In et al, 2019), and .80 (Anderson-Butcher et al, 2013). In the current study, the Cronbach's alpha was .65, and the reliability of composite scores was .70.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Items are rated on a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). A range of Cronbach's alphas have been reported for this subscale: .70 (Carney, Liu, & Hazler, 2018), .74 (In et al, 2019), and .80 (Anderson-Butcher et al, 2013). In the current study, the Cronbach's alpha was .65, and the reliability of composite scores was .70.…”
Section: Methodsmentioning
confidence: 97%
“…Students' perceived acceptance of diversity was found to be positively associated with their connectedness to school (Carney, Liu, & Hazler, 2018). In a recent study, In et al (2019) found that social skills and perceived diversity at school accounted for 33.5% of the variance in school connectedness.…”
Section: Acceptance Of Diversitymentioning
confidence: 95%
“…Although previous studies have revealed relationships between student cynicism and students' life satisfaction, the relationships between the sub-scales of student cynicism and the sub-scales of students' life satisfaction could not be identified. Although there is no research that address the relationship between student cynicism and demographic variables such as gender and age in the literature, research has been conducted on its relationship with student life satisfaction (Farwa, Hussain, Afzal, & Gilani, 2019;Hawi & Samaha, 2017;In, Kim & Carney, 2019;Santos, Sarriera & Bedin, 2019;Zappulla, Pace, Lo Cascio, et al, 2014). However, even though it is possible to find a variety of studies addressing life satisfaction of high school students (Kapıkıran & Şahin, 2012, Koçak & İçmenoğlu, 2012, no studies have been found that centers on student cynicism at high school level.…”
Section: Introductionmentioning
confidence: 99%
“…An impact on several areas of life, both present and future, is observed in students who have low life satisfaction (Nishida et al, 2016). This includes aspects such as their social relationships (Forrest et al, 2013), social skills (In et al, 2019), their school performance (Forrest et al, 2013), their strengths (Cherry et al, 2020), and their self-efficacy (Cherry & Lumley, 2019), among others. Besides, positive affects, essential to a child's wellbeing, predict satisfaction in adult life (Coffey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%